A Pareto improved artificial fish swarm algorithm for solving a multi-objective fuzzy disassembly line balancing problem - Zhang, Zeqiang; Wang, Kaipu; Zhu, Lixia; Wang, Yi (Expert systems with applications, 2017)
•Multi-objective fuzzy disassembly line balancing problem is studied.•An improved Pareto based artificial fish swarm algorithm is proposed.•The Pareto set provides the diversity of non-inferior solutions.•Comparison with an existing algorithm proves the superiority of the proposed method.•The practicality of the proposed method is confirmed through an actual instance. To better reflect the uncertainty existing in the actual disassembly environment, the multi-objective disassembly line balancing problem with fuzzy disassembly times is investigated in this paper. First, a mathematical model of the multi-objective fuzzy disassembly line balancing problem (MFDLBP) is presented, in which task disassembly times are assumed as triangular fuzzy numbers (TFNs). Then a Pareto improved artificial fish swarm algorithm (IAFSA) is proposed to solve the problem. The proposed algorithm is inspired from the food searching behaviors of fish including prey, swarm and follow behaviors. An order crossover operator of the traditional genetic algorithm is employed in the prey stage. The Pareto optimal solutions filter mechanism is adopted to filter non-inferior solutions. The proposed model after the defuzzification is validated by the LINGO solver. And the validity and the superiority of the proposed algorithm are proved by comparing with a kind of hybrid discrete artificial bee colony (HDABC) algorithm using two test problems. Finally, the proposed algorithm is applied to a printer disassembly instance including 55 disassembly tasks, for which the computational results containing 12 non-inferior solutions further confirm the practicality of the proposed Pareto IAFSA in solving the MFDLBP.